Buletin Peternakan : PENGARUH SUHU AIR PENCUCIAN AMBING DAN TEAT DIPPING TERHADAP JUMLAH PRODUKSI, KUALITAS DAN JUMLAH SEL SOMATIK SUSU PADA SAPI PERANAKAN FRIESIAN HOLSTEIN - HAPPY APRILLIA MAHARDIKA (Peternakan UGM, 2016)
This study aimed to investigate the effect of teat dipping on the number of microorganisms based on reductase test and somatic cell, as well as determine the effect udder wash water temperature (temperature of 19-22 Â°C and 37 Â°C) on the quality of milk components and quantity of milk production in cows PFH located in KOP SAE Pujon.